2014
DOI: 10.12927/hcpol.2014.23940
|View full text |Cite
|
Sign up to set email alerts
|

Media Coverage of Youth Suicides and Its Impact on Paediatric Mental Health Emergency Department Presentations

Abstract: Background: To examine mental health (MH) presentations to the emergency department (ED) of a paediatric hospital following two highly publicized local teen suicides. Methods: Youths aged 12-18 years with a MH chief complaint and/or diagnosis were included. Differences in frequencies were analyzed using chi-square tests, and relative risks were evaluated using generalized linear modelling. Results: Significant increases in the number of ED presentations were found within the months of the publicized suicides c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 16 publications
0
6
1
Order By: Relevance
“…Among children age 12-18 years, the authors found a significant increase in ED presentations for mental illness, substance misuse or abuse, and intentional selfharm, but no significant effect on suicidal status (ideation, plan, gesture or attempt) or psychiatric hospitalization rate. 4 Their findings were somewhat contradictory to ours and may be due to differences in the sampling frame. Leon et al studied ED visits at a single Canadian academic centre within a narrow geographic region of Ontario, in contrast to our sample which included all Ontario EDs, possibly making an association easier to observe.…”
Section: Suicidal Behaviour and The Internet Discussioncontrasting
confidence: 57%
See 2 more Smart Citations
“…Among children age 12-18 years, the authors found a significant increase in ED presentations for mental illness, substance misuse or abuse, and intentional selfharm, but no significant effect on suicidal status (ideation, plan, gesture or attempt) or psychiatric hospitalization rate. 4 Their findings were somewhat contradictory to ours and may be due to differences in the sampling frame. Leon et al studied ED visits at a single Canadian academic centre within a narrow geographic region of Ontario, in contrast to our sample which included all Ontario EDs, possibly making an association easier to observe.…”
Section: Suicidal Behaviour and The Internet Discussioncontrasting
confidence: 57%
“…Using aggregate data, we identified all patients age 11-17 years who presented to Ontario EDs using International Classification of Disease and Health Related Problems, Tenth Revision, Canada (ICD-10-CA) codes for suicidal ideation (R45.851), intentional self-poisoning (X60-X69) and intentional self-harm (X70-X84). These discharge diagnoses were used previously to explore the impact of media coverage on adolescent suicidal behaviour 4,19,20 and were chosen because we felt they comprehensively encompassed the range of suicide-related behaviour. Self-harm encompasses suicidal attempts 20 and is a major risk factor for suicide.…”
Section: Methods Designmentioning
confidence: 99%
See 1 more Smart Citation
“…Almost 10% of submissions reported self‐diagnosis after viewing a media report. Media influence on increasing diagnosis and clinical presentations has been described in influenza and in particular mental health, where media coverage of suicides can lead to increased at‐risk presentations and suicides . A patient who feels let‐down by mainstream medicine may personally identify with the generally sensationalised, but ultimately hopeful, tone of many of these media reports, and then seek a similar diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Among prevention actions recommended as efficient, the WHO promotes the empowerment of media professionals in reporting on suicide-related events. For more than half a century, the literature has indeed provided robust evidence that incautious media coverage of suicide is associated with a substantial increase of suicide rates, especially in young populations ( Phillips, 1974 ; Leon et al, 2014 ) and/or when a celebrity in involved ( Niederkrotenthaler et al, 2020 ). Detrimental consequences of suicide-related reports have been tagged “Werther Effect” (WE) in reference to the European suicide epidemy that followed the publication of Goethes’ Sorrow of the Young Werther ( Von Goethe, 1774 ).…”
Section: Introductionmentioning
confidence: 99%